2009
DOI: 10.1523/jneurosci.3054-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Brain Activity during Prism Adaptation

Abstract: Prism adaptation does not only induce short-term sensorimotor plasticity, but also longer-term reorganization in the neural representation of space. We used event-related fMRI to study dynamic changes in brain activity during both early and prolonged exposure to visual prisms. Participants performed a pointing task before, during, and after prism exposure. Measures of trial-by-trial pointing errors and corrections allowed parametric analyses of brain activity as a function of performance. We show that during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
187
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(210 citation statements)
references
References 47 publications
20
187
2
1
Order By: Relevance
“…The neural correlates of sensorimotor adaptation have been investigated from various viewpoints, such as sensorimotor plasticity and motor learning. [17][18][19] Contrary to our expectations, most of these studies have proposed the importance of the cerebellum and the parietal cortex for sensorimotor adaptation. Too little has been reported on the involvement of the PFC.…”
Section: Introductioncontrasting
confidence: 85%
“…The neural correlates of sensorimotor adaptation have been investigated from various viewpoints, such as sensorimotor plasticity and motor learning. [17][18][19] Contrary to our expectations, most of these studies have proposed the importance of the cerebellum and the parietal cortex for sensorimotor adaptation. Too little has been reported on the involvement of the PFC.…”
Section: Introductioncontrasting
confidence: 85%
“…These effects suggest rapid plasticity mechanisms and cerebral reorganisation in response to the visuo-motor mismatch. Interestingly, a recent fMRI study of prism adaptation in healthy participants (Luaute et al, 2009) reported that the magnitude of error produced by prismatic shift was correlated with activation of the ACC, consistent with the notion that this region plays crucial role in error detection (Kerns et al, 2004).…”
Section: Introductionsupporting
confidence: 56%
“…A role for the PPC during reaching prism adaptation tasks is also supported by lesion studies (Pisella et al 2004). Activity in the cerebellum has been shown to increase during the early phase of prism exposure such that it is elevated in late prism adaptation compared with early adaptation and remains higher for longer durations compared with the PPC (Chapman et al 2010;Luauté et al 2009). Results in patients with cerebellar lesions also support this idea, as they lack the ability to adapt to prismatic displacement during a throwing task (Martin et al 1996a).…”
Section: Discussionmentioning
confidence: 90%
“…Although several brain regions are most likely at work during prism adaptation, two structures in particular have emerged as playing a dominant role: the PPC and the cerebellum. Recent neuroimaging studies found that the anterior intraparietal sulcus (AIP) is active in the early phase of prism exposure when reaching error is high (Chapman et al 2010;Clower et al 1996;Danckert et al 2008;Luauté et al 2009). Luauté et al (2009) suggest that AIP is involved in error detection since its activity is related to the trial-by-trial size of reaching error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation